Epidemiology of Primary Immunodeficiencies in Ukraine according to the Register of Patients - L.I. Chernyshova; A.V. Bondarenko; L.V. Kostyuchenko; O.M. Savvo; A.P. Volokha; O.V. Rabosh (Zaslavsky O.Yu., 2015)
Primary immunodeficiencies (PID) are a group of rare immune congenital disorders. Detection of PID, counting their number and nosology identification are important problems of pediatrics as it is important for the development of measures for diagnosis and treatment. The objective of this work was to study the incidence of PID in Ukraine and its nosologic forms by creating a registry of patients. Information about all patients with PID diagnosed during the 1995-2014 was collected in 27 administrative centers of Ukraine. At the beginning of 2015, the register included 814 patients, 684 of them - alive, among them 561 children and 123 patients older than 18 years. The minimal incidence of PID is 1.23 alive patients per 100,000, minimal incidence of giving birth to a child with PID - 9.94 per 100,000 live births. In Ukraine, the structure of PID in terms of immune system impairment is close to that of worldwide, the main groups of PID are presented with 39 nosological forms. The findings suggest a lack of PID detection in Ukraine, so the issue of increased alertness in doctors of different specialties concerning PID and timely referral of patients to child immunologist remains topical.